2017
DOI: 10.1021/acsami.7b14078
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Graphene Foam Induces Multifunctionality in Epoxy Nanocomposites by Simultaneous Improvement in Mechanical, Thermal, and Electrical Properties

Abstract: Three-dimensional (3D) macroporous graphene foam based multifunctional epoxy composites are developed in this study. Facile dip-coating and mold-casting techniques are employed to engineer microstructures with tailorable thermal, mechanical, and electrical properties. These processing techniques allow capillarity-induced equilibrium filling of graphene foam branches, creating epoxy/graphene interfaces with minimal separation. Addition of 2 wt % graphene foam enhances the glass transition temperature of epoxy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…As a result, the MSR/ GrF/Ecoflex composite ruptures at a stress of 186.8 kPa and a stretch of 601.7%. It is reported that the GrF aids in load-bearing, increasing the ultimate tensile strength and ductility while composited with the elastic polymer [27]. Therefore, the stretchability and strength of the assembled device are combination of the two elastomer and closer to Ecoflex.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the MSR/ GrF/Ecoflex composite ruptures at a stress of 186.8 kPa and a stretch of 601.7%. It is reported that the GrF aids in load-bearing, increasing the ultimate tensile strength and ductility while composited with the elastic polymer [27]. Therefore, the stretchability and strength of the assembled device are combination of the two elastomer and closer to Ecoflex.…”
Section: Resultsmentioning
confidence: 99%
“…The pristine freestanding GrF shown in Figure 3c offers filler properties such as ultra-low density (<4 mg/cm 3 ), enhanced surface area (~850 m 2 /g), and improved electron and phonon conduction due to reduced inter Gr sheet contact resistance [21][22][23][24]. As a result, 3D GrF has been used in producing several composite materials for applications such as scaffolds [21], strain sensors [16], vibration dampeners [12,25], supercapacitors [26], fracture-resistant materials [27], and thermal interfacing [28]. The pristine 3D GrF is often fabricated via a template-directed chemical vapor disposition (CVD) technique [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, 3D GrF has been used in producing several composite materials for applications such as scaffolds [21], strain sensors [16], vibration dampeners [12,25], supercapacitors [26], fracture-resistant materials [27], and thermal interfacing [28]. The pristine 3D GrF is often fabricated via a template-directed chemical vapor disposition (CVD) technique [24][25][26][27][28]. Since its advent in 2011, from the trend analysis of scientific publications on CVD GrF (Figure 4, data from the web of science), it is evident that there is a tremendous interest in tapping into intrinsic properties of graphene arranged in a 3D hierarchical structure.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In addition, due to the exibility and biocompatibility, graphene can be a promising material for high-performance, multifunctional wearable electronics and biomedical applications. 17,18 However, the application of graphene in practical wearable electronics is challenging due to its electrical properties under high tensile conditions. 7,15,19 Chen et al manufactured 3D interconnected graphene networks by chemical vapor deposition, embedding these networks in a polydimethylsiloxane (PDMS) matrix to produce strain sensors capable of withstanding tensile strains up to 95% and providing a gauge factor of 2.…”
Section: Introductionmentioning
confidence: 99%